Differences in Patient Satisfaction between BPJS and Non-BPJS Patients Regarding Service Quality in the Internal Medicine Outpatient Clinic (Journal of Social And Education Research, 2024)
One of the indicators of successful health service delivery is the improvement of service quality without discrimination. In Indonesia, there are public perceptions regarding differential treatment between BPJS (national health insurance) and non-BPJS patients. This study aimed to examine differences in patient satisfaction between BPJS and non-BPJS patients regarding service quality at the Internal Medicine Outpatient Clinic of Patut-Patuh Patju Regional General Hospital, West Lombok Regency. This research employed a quantitative comparative design with a total sample of 100 respondents. The results showed that the proportion of patients reporting dissatisfaction was higher among BPJS patients compared to non-BPJS patients. Specifically, 47 BPJS patients (94%) expressed satisfaction, while 3 patients (6%) were dissatisfied. In contrast, among non-BPJS patients, 49 (98%) reported satisfaction and 1 (2%) expressed dissatisfaction. Statistical analysis using the Mann-Whitney test indicated no significant difference in patient satisfaction between BPJS and non-BPJS patients, with an Asymp. Sig (2-tailed) value of 0.05. These findings suggest that while minor differences in satisfaction levels exist, overall patient satisfaction does not significantly differ between the two groups, highlighting the hospital’s effectiveness in providing equitable health services.